Le fédéralisme financier en Allemagne: coopération ou concurrence? - Lars P. Feld (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
In this paper, German federalism is analysed with respect to its implications for public spending and revenue. Since the Second World War, taxing and spending competencies in Germany have become more and more centralised. This is demonstrated with respect to (1) changes of the power to tax, (2) the important territorial reforms, and (3) the increase of the federal influence on spending of sub-federal jurisdictions. In addition, the fiscal equalization system between jurisdictions is too egalitarian and the effects of German fiscal federalism on regional development are disastrous. Compared to unitary states with a powerful central government, this kind of cooperative federalism has the disadvantage of a federal state which cannot often decide anything without the consent of the states. Consequently, many reforms are blocked in the struggle between Bundestag and Bundesrat. It appears that only the introduction of fiscal competition between the states is able to improve economic policy in Germany.
Keywords: 330; Finanzföderalismus; Finanzausgleich; Deutschland